The immune regulatory role of exosomal miRNAs and their clinical application potential in heart failure - Guo, Dandan; Yan, Junchen; Yang, Zhenyu; Chen, Mengzhu; Zhong, Weibo; Yuan, Xingxing; Yu, Siming (Frontiers in Immunology, 2024)
Heart failure (HF) is a complex and debilitating condition characterized by the heart’s inability to pump blood effectively, leading to significant morbidity and mortality. The abnormality of immune response is a key factor in the progression of HF, contributing to adverse cardiac remodeling and dysfunction. Exosomal microRNAs (miRNAs) play a pivotal role in regulating gene expression and cellular function, which are integral to the crosstalk between cardiac and immune cells, influencing immune cell functions, such as macrophage polarization, T cell activity, and cytokine production, thereby modulating various pathological processes of HF, such as inflammation, fibrosis, and cardiac dysfunction. This review emphasizes the immune-regulatory role of exosomal miRNAs in HF and highlights their clinical potential as diagnostic biomarkers and therapeutic agents.